3x-12=1x-14

Simple and best practice solution for 3x-12=1x-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-12=1x-14 equation:


Simplifying
3x + -12 = 1x + -14

Reorder the terms:
-12 + 3x = 1x + -14

Reorder the terms:
-12 + 3x = -14 + 1x

Solving
-12 + 3x = -14 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-12 + 3x + -1x = -14 + 1x + -1x

Combine like terms: 3x + -1x = 2x
-12 + 2x = -14 + 1x + -1x

Combine like terms: 1x + -1x = 0
-12 + 2x = -14 + 0
-12 + 2x = -14

Add '12' to each side of the equation.
-12 + 12 + 2x = -14 + 12

Combine like terms: -12 + 12 = 0
0 + 2x = -14 + 12
2x = -14 + 12

Combine like terms: -14 + 12 = -2
2x = -2

Divide each side by '2'.
x = -1

Simplifying
x = -1

See similar equations:

| y=57+9 | | 3x+4=x-4 | | 14-47=4(x-4)-5 | | 4x^2+5x+1=85 | | (x-18)/x=0.75 | | v+6=8/9 | | (18-x)/x=0.75 | | 5X+Y+Z=365 | | 5X+Y+Z=360 | | 3z-6=9z+18 | | -4v-12=8(v-9) | | 4a^9+4=0 | | (3y+2)(4y+1)=6y+5 | | 6x^2-30x+13=0 | | (2i+9j)+(7i-3j)= | | x^3-27/y^3=0 | | ln(x)=3/4 | | 4.8+x-5.9=3.6 | | 5(x+4)-4x=18-23 | | y=100-10(-63.24) | | 6+-6(3x+-1)=-42 | | 6+-6(3x+-1)=42 | | 3/5t+7=8 | | -7v-2=5v^2 | | -5.25r=332 | | 32-6x+7x=-15+28 | | 5(4z)-0.5z=234 | | 3/4x-6/7x=0 | | 53-5/8x=102 | | 16+x-11=18-5 | | 6y^3+3y^2-18y=0 | | 4ln(x)-3=0 |

Equations solver categories